1997
DOI: 10.1159/000237453
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Ozone and Allergen Challenges on Bronchial Responsiveness and Inflammation in Sensitised Guinea Pigs

Abstract: Background: Environmental pollutants such as ozone may interact with airway responses to allergen in sensitised individuals. Methods: We examined the effects of a single exposure to ozone (1 ppm for 1 h) on bronchial responsiveness to acetylcholine (ACh) aerosol 3 and 24 h after single ovalbumin (OA) challenge in OA-sensitised anaesthetised guinea pigs. Broncho-alveolar lavage (BAL) was performed and protein content and differential cell counts were determined. Results: Ozone increased bronchial responsiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Currently, more and more evidences show that a long-term exposure to high concentrations of ozone in the environment may be harmful to the human body, which may cause permanent damage to lungs, especially for small children, patients with asthma, and the elderly. (Folinsbee et al, 1988;Horstman et al, 1990;Jorres et al, 1996;Kehrl et al, 1999;Molfino et al, 1991;Peden et al, 1995;Roux et al, 1999;Sun et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, more and more evidences show that a long-term exposure to high concentrations of ozone in the environment may be harmful to the human body, which may cause permanent damage to lungs, especially for small children, patients with asthma, and the elderly. (Folinsbee et al, 1988;Horstman et al, 1990;Jorres et al, 1996;Kehrl et al, 1999;Molfino et al, 1991;Peden et al, 1995;Roux et al, 1999;Sun et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…As the third most important greenhouse gas and one of the most important components of photochemical smog, tropospheric ozone originates from the stratosphere and troposphere exchange (STE) process and photochemical reactions involving its precursors, such as nitrogen dioxides (NO x = NO + NO 2 ), volatile organic compounds (VOCs), CO and CH 4 [1]. High concentrations of ozone have adverse effects on human health and ecosystem productivity near the surface layer [2][3][4][5][6][7][8]. Therefore, understanding and measuring ozone and its precursors has become more important, and tropospheric ozone has already been included as a routine monitoring component in the new air quality standard of 2013 (http://kjs.mep.gov.cn/).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies have demonstrated an enhanced IgE production to allergen upon exposure to diesel exhaust particles [5]. Exposure to nitrogen dioxide, ozone and diesel particles have all been associated with increased airway responsiveness to allergen challenge in animal or chamber studies [6–10]. Collectively therefore these data suggest that the effects of various pollutants and aeroallergens might interact, but whether this occurs at ambient concentrations and pollutant aeroallergen mixtures, and how relatively important these interactions are to asthma morbidity at the individual or population level is unknown.…”
Section: Introductionmentioning
confidence: 99%